Video Konten Edukasi Pembelajaran Pada Akun Tiktok@mayatoomuch Sebagai Sarana Ekspresi Diri - Dwijayanti, Risqi Inayah; Kesuma, Hendrik (FISIP Universitas Bung Karno, 2024)
Self-existence is a condition of a person with the ability to find meaning in life. The purpose of this study was to determine Self-Existence through the Tik-Tok Application in Learning Educational Video Content on the @mayatoomuch Account. The theoretical basis used is the Symbolic Interaction Theory and uses the Conceptual Basis, Social Media, Tik Tok Applications, Self-Concept and Self-Existence. The approach used in this research is qualitative. Constructivism Paradigm. Phenomenological Method. Using data collection techniques in the form of observation, interviews, documentation and triangulation. The results of this study indicate that Maya Rachmawaty's self-existence uses 4 components of Edmund Husserl's Phenomenology, namely intentionality, noema and noesis, intuition, and intersubjectivity. Self-existence through the Tik Tok application includes the many users of the Tik Tok application who have many followers, but disappear again because there are no followers or followers turning to other people's accounts.Keywords : Self-Existence, Tik Tok Application, Learning Education